High incidence of post‐transplant cytomegalovirus reactivations in myeloma patients undergoing autologous stem cell transplantation after treatment with bortezomib‐based regimens: a survey from the Rome Transplant Network. Issue 1 (12th November 2013) - Marchesi, F.; Mengarelli, A.; Giannotti, F.; Tendas, A.; Anaclerico, B.; Porrini, R.; Picardi, A.; Cerchiara, E.; Dentamaro, T.; Chierichini, A.; Romeo, A.; Cudillo, L.; et al.
Abstract The incidence of cytomegalovirus (CMV) reactivations in patients with multiple myeloma (MM) receiving autologous stem cell transplantation (ASCT) is relatively low. However, the recent increased use of novel agents, such as bortezomib and/or immunomodulators, before transplant, has led to an increasing incidence of Herpesviridae family virus infections. The aim of the study was to establish the incidence of post‐engraftment symptomatic CMV reactivations in MM patients receiving ASCT, and to compare this incidence with that of patients treated with novel agents or with conventional chemotherapy before transplant. The study was a survey of 80 consecutive patients who underwent ASCT after treatment with novel agents (Group A). These patients were compared with a cohort of 89 patients treated with VAD regimen (vincristine, doxorubicin, and dexamethasone) before ASCT (Group B). Overall, 7 patients (4.1%) received an antiviral treatment for a symptomatic CMV reactivation and 1 died. The incidence of CMV reactivations was significantly higher in Group A than in Group B (7.5% vs. 1.1%; P = 0.048). When compared with Group B, the CMV reactivations observed in Group A were significantly more frequent in patients who received bortezomib, whether or not associated with immunomodulators (9.4% vs. 1.1%; P = 0.019), but not in those treated with immunomodulators only (3.7% vs. 1.1%; P = 0.396). These results suggest that MM patients treated with bortezomib‐based regimens are at higher risk of developing a symptomatic CMV reactivation after ASCT.